PENGARUH KUALITAS LAYANAN DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN MELALUI BRAND IMAGE SEBAGAI VARIABEL INTERVENING (Studi kasus pada Brand Vamo di Yogyakarta) - Hendrian Rachmad Alif Viando; Nonik Kusuma Ningrum; Putri Dwi Cahyani (Universitas Bina Taruna Gorontalo, 2023)
This study aims to determine whether there is an influence of service quality and product quality on purchasing decisions through brand image as an intervening variable on the Vamo brand. The population used in this study were people who had purchased Vamo products in the city of Yogyakarta. This study uses a type of questionnaire that uses the Google form as a research tool. The research method used is purposive sampling technique. The sample used was 100 respondents. The data obtained from the questionnaire were then processed and analyzed using Multiple Linear Regression analysis with model accuracy (classical assumption test), hypothesis testing using the partial test (t) and determination test (R2) using the SPSS 25 program. The results in this study indicate that the variable service quality has a positive and significant effect on brand image, product quality has a positive and significant effect on brand image, service quality has a positive and significant effect on purchasing decisions, product quality has no effect on purchasing decisions, and brand image has a positive and significant effect on purchasing decisions.